Faktor Determinan Pemerintah Singapura dalam Keberhasilannya Menanggulangi Isu Perdagangan Manusia (2009-2023) - Farhah, Jasmine Zahra; Wicaksono, Arief (Universitas Bosowa, 2025)
Singapore is a country known as a regional economic center with a high and good standard of living. However, despite this progress, Singapore still cannot escape the problem of human trafficking. Human trafficking is a transnational issue that occurs very often but is challenging to detect. The most common forms of human trafficking in Singapore are sex trafficking and forced labor. Singapore has made various efforts in dealing with human trafficking and has succeeded in moving up to Tier 1 in the TIP Reports since 2020. These findings will explain the factors that support Singapore’s success in dealing with human trafficking from a conceptual perspective with the idea of a basic framework for combating human trafficking or “4Ps” according to the Trafficking Victims Protection Reauthorization Act (TVPRA uses a descriptive qualitative method, namely containing the 4P factors, the active role of government and NGOs, cultural influences, population, and the encouragement of the national image. This research also discusses the dark side of Singapore in Human trafficking often occurs in Singapore’s red-light district, Geylang, as well as the reality of forced labor, which is inversely proportional to Singapore’s position in Tier 1.